Constraint-Induced Movement Therapy for Improving Motor Function of the Paretic Lower Extremity After Stroke. (June 2020) - dos Anjos, Sarah M.; Morris, David M.; Taub, Edward
Abstract : Abstract: A 56-yr-old woman with chronic stroke and gait dysfunction was recruited for this study. A lower-extremity constraint-induced movement therapy protocol was given consisting of 3.5 hrs/d of supervised intervention activities on 10 consecutive weekdays. Motor training was intensive and involved shaping. In addition, a group of behavior management strategies was used to induce further unsupervised practice and transference of motor skills from the laboratory to real-world situations. Changes in functional mobility, walking speed, balance, level of assistance, perceived quality of movement, and level of confidence while performing daily activities were assessed five times in both the baseline and intervention phases. The outcomes observed after the intervention were determined by calculating the difference between the average scores obtained in both phases. Changes in perceived quality of movement, level of confidence, level of assistance, and balance were observed. Abstract : Supplemental digital content is available in the text.